Enhancing Teacher Organizational Commitment Through Authentic Leadership, Integrity, Teamwork, and Trust - Christine Masada Hirashita Tobing; Sri Setyaningsih; Dian Wulandari (SUJANA: Education and Learning Review, 2026)
This study investigated the direct and indirect effects of authentic leadership, integrity, and teamwork on organizational commitment through the mediating role of trust among private senior high school teachers. Using path analysis, data were collected from 135 teachers across 15 private senior high schools in Depok, Indonesia, selected through multistage random sampling. Results demonstrated that authentic leadership, integrity, and teamwork significantly predicted organizational commitment both directly and indirectly through trust. Authentic leadership exhibited the strongest total effect (β = 0.309), followed by integrity (β = 0.275) and teamwork (β = 0.273). Trust significantly mediated relationships between all three predictors and organizational commitment, though indirect effects were relatively modest compared to direct pathways. The predictor variables collectively explained 91.3% of variance in organizational commitment through direct effects and an additional 17.1% through trust-mediated pathways. SITOREM analysis identified priority intervention areas including strengthening continuance commitment dimensions, enhancing leader authenticity in daily interactions, and fostering collaborative climates characterized by openness and mutual support. Findings provide empirical support for multifaceted intervention strategies targeting leadership development, organizational integrity, and collaborative practices to enhance teacher commitment in private educational institutions. The study advances theoretical understanding of commitment formation mechanisms while offering practical guidance for educational administrators seeking to improve teacher retention and institutional effectiveness in Southeast Asian contexts.